PENERAPAN SANITASI PASAR UNGGAS DI WILAYAH DINAS PERINDUSTRIAN, PERDAGANGAN, KOPERASI DAN PERTANIAN KOTA YOGYAKARTA - , RISKI WIRA IRYANTI; , drh. Heru Susetya, MP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Poultry market has a risk of spread of avian diseases in both the are zoonotic or not. Prevention and control of poultry diseases can be done by applying a good and proper sanitation in the poultry market. Job Training was conducted to determine the application Disperindagkoptan sanitation conducted by the city of Yogyakarta and the poultry traders in the poultry market. Locations used in the data collection is Poultry Market Terban, Gondokusuman, Yogyakarta. The material observed is action sanitary poultry markets and traders conducted by Disperindagkoptanpoultry, poultry traders hygiene, cleanliness visitors poultry, as well as sanitary poultry itself. Performed by the application of sanitary Disperindagkoptan of Yogyakarta by spraying desinfectant on cages and equipment in Poultry Marketof Terban still need to be repaired, this is because not followed by good cooperation between Disperindagkoptan of Yogyakarta with poultry traders so that the implementation is done sanitation becomes less efficient. To hygiene of poultry traders, washing hands and feet have been done although not all of them, but equipment such as masks